Միջնադարեան հայ կոմպոզիտորներ - Արամ Երեմեան (Տպարան Սրբոյ Յակոբեանց)
Բ. Հնագոյն հայ երաժշտագէտներ 4-5 դար
Keywords: Auxiliary Sciences of History; Medieval History; History; Biography; Music and Books on Music; Music